1999
DOI: 10.1152/jn.1999.81.4.1795
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Anesthesia Revealed by Shunting Actions of Isoflurane on Thalamocortical Neurons

Abstract: By using thalamic brain slices from juvenile rats and the whole cell recording technique, we determined the effects of aqueous applications of the anesthetic isoflurane (IFL) on tonic and burst firing activities of ventrobasal relay neurons. At concentrations equivalent to those used for in vivo anesthesia, IFL induced a hyperpolarization and increased membrane conductance in a reversible and concentration-dependent manner (ionic mechanism detailed in companion paper). The increased conductance short-circuited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(111 citation statements)
references
References 39 publications
(38 reference statements)
5
105
1
Order By: Relevance
“…115 This observation appears to be at odds with the data from human electroencephalography mentioned just before. In further support of the thalamus as a target of anesthetics, halothane and isoflurane have been shown to hyperpolarize thalamocortical neurons in vitro, 116,117 and GABA agonists injected into the intralaminar thalamic nuclei cause a loss of the righting reflex (considered a behavioral correlate of a loss of consciousness) in rats. 118 Moreover, Alkire's group recently demonstrated that rats under general anesthesia can be awakened by injections of nicotine into the intralaminar nuclei 119 or by the infusion of an antibody against a voltagegated potassium channel in the same location.…”
Section: The "Thalamic Consciousness Switch"mentioning
confidence: 99%
“…115 This observation appears to be at odds with the data from human electroencephalography mentioned just before. In further support of the thalamus as a target of anesthetics, halothane and isoflurane have been shown to hyperpolarize thalamocortical neurons in vitro, 116,117 and GABA agonists injected into the intralaminar thalamic nuclei cause a loss of the righting reflex (considered a behavioral correlate of a loss of consciousness) in rats. 118 Moreover, Alkire's group recently demonstrated that rats under general anesthesia can be awakened by injections of nicotine into the intralaminar nuclei 119 or by the infusion of an antibody against a voltagegated potassium channel in the same location.…”
Section: The "Thalamic Consciousness Switch"mentioning
confidence: 99%
“…64 A study that concluded that cortical changes in the EEG preceded changes in thalamic local field potentials at loss of consciousness supports this view but, interestingly, a recent study concluded the opposite during sleep onset. 65 Alternatively, anesthetics are known to hyperpolarize thalamocortical neurons, [66][67][68][69][70] and this could lead directly to the delta oscillations and spindle activity that are observed during anesthesia. Since the pattern of cortical deactivation that is seen during anesthesia resembles that of natural sleep, it seems more plausible to us that anesthetic effects at the level of the thalamus, or on the arousal pathways that modulate thalamic activity, are responsible for coordinating the overall network response.…”
Section: Sleep and General Anesthesia 143mentioning
confidence: 99%
“…Using previously described procedures (Ries and Puil 1999;Tennigkeit et al 1996), coronal slices (approximately 300 m) containing the ventral portion of the medial geniculate body (MGB) were prepared from brain tissue of anesthetized Sprague-Dawley rats (13-15 days). Most recordings were made in neurons from P14 rats.…”
Section: E T H O D Smentioning
confidence: 99%
“…The junction potential of Ϫ11 mV was subtracted from all membrane potentials, e.g., a recorded resting potential of Ϫ55 mV corresponds to an actual potential of Ϫ66 mV (see Ries and Puil 1999;Zhang and Krnjevic 1993). The data were analyzed with pClamp 8 (Clampfit, Axon Instruments) or Prism GraphPad software (v. 2.0, San Diego, CA).…”
Section: Data and Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation